Latin American Lending by Major U.S. Banks: The Effects of Disclosures about Nonaccrual Loans and Loan Loss Provisions. - Griffin, Paul A.; Wallach, Samoa J.R. (The Accounting Review, 1991)
Abstract Examines how stockholders' returns of 13 of the largest American money-center and regional banks were affected by disclosures made during 1987 regarding decisions to place Brazilian loans on a nonaccrual basis and to increase loan loss reserves to recognize the higher probability of default and the lower present value of future interest and principal.